Modulating chromatin structure and DNA accessibility by deacetylase inhibition enhances the anti-cancer activity of silver nanoparticles - Igaz Nóra; Kovács Dávid; Rázga Zsolt; Kónya Zoltán; Boros Imre Miklós; Csontné Kiricsi Mónika (2016)
Abstract Histone deacetylase (HDAC) inhibitors are considered as novel therapeutic agents inducing cell cycle arrest and apoptotic cell death in various cancer cells. Inhibition of deacetylase activity results in a relaxed chromatin structure thereby rendering the genetic material more vulnerable to DNA targeting agents that could be exploited by combinational cancer therapy. The unique potential of silver nanoparticles (AgNPs) in tumor therapy relies on the generation of reactive radicals which trigger oxidative stress, DNA damage and apoptosis in cancer cells. The revolutionary application of AgNPs as chemotherapeutical drugs seems very promising, nevertheless the exact molecular mechanisms of AgNP action in combination with other anti-cancer agents have yet to be elucidated in details before clinical administrations. As a step towards this we investigated the combinational effect of HDAC inhibition and AgNP administration in HeLa cervical cancer cells. We identified synergistic inhibition of cancer cell growth and migration upon combinational treatments. Here we report that the HDAC inhibitor Trichostatin A enhances the DNA targeting capacity and apoptosis inducing efficacy of AgNPs most probably due to its effect on chromatin condensation. These results point to the potential benefits of combinational application of HDAC inhibitors and AgNPs in novel cancer medication protocols.